ANALISIS BAHASA KIASAN YANG DIGUNAKAN DALAM FILM “THE ADVENTURE OF TOM SAWYER” - Ricky, Ricky; Ambalegin, Ambalegin; Arianto, Tomi (eScience Humanity Journal, 2024)
Movies are popular forms of entertainment for younger individuals and a useful instruments for language learning. This study focuses on semantics, specifically the use of metaphorical language in the film "The Adventures of Tom Sawyer." Semantics is a method of linguistics that studies meaning, including synonyms, antonyms, word meanings, and word relationships. This study used a qualitative research method to detect different types of metaphorical language in the movie script. The qualitative approach entails analyzing data using words and utterances, whereas the data was collected and analyzed using methodology and observation. The study approach consisted of watching the film, analyzing the transcript, and identifying metaphorical terms. The researchers used a non-participant technique, in which they studied the movie transcript without directly interacting with the subjects. The study identified and classified 13 instances of figurative language, including 1 simile (7.7%), 2 metaphors (15.4%), 2 personifications (15.4%), 2 hyperboles (15.4%), 2 occurrences of irony (15.4%), 2 cases of symbolism (15.4%), 1 paradox (7.7%), and 1 litotes (7.7%). The findings highlight the film's varied use of figurative language, which enriches the story and improves comprehension, making it an interesting medium for language learners.